Teacher Strategies in Developing Social and Emotional Skills of Early Childhood at Tunas Harapan Early Childhood Education, Meribung Village, Limun District, Sarolangun Regency - Elvi Elvi; Fiqi Nurmanda Sari; Atika Wirdasari (The Future of Education Journal, 2026)
This thesis discusses teacher strategies in developing the social and emotional skills of early childhood at Tunas Harapan Early Childhood Education (PAUD), Meribung Village, Limun District, Sarolangun Regency. Social and emotional development is very important and needs to be stimulated from an early age. Parents play an important role in children’s development, especially in their social and emotional development. The goal is for children to be able to manage their social and emotional well-being. Thils study usels qualitative researchl with al case studyl lapproach. Datal collection techniquesl include lobservation, linterviews, andl ldocumentation. Datal analysis techniquesl consist ofl data lcollection, datal lreduction, datal lpresentation, andl drawing lconclusions. The lresults ofl this studyl indicate thatl teacher strategiesl to developl children’s sociall and emotionall lwell-beingl can bel limplemented throughl role-playing methods, storytelling, and cooperative learning.